E. coli HMS174(DE3) is a sustainable alternative to BL21(DE3) - Hausjell, Johanna (Microb Cell Fact, 2018)
BACKGROUND: Escherichia coli is one of the most widely used hosts for recombinant protein production in academia and industry. Strain BL21(DE3) is frequently employed due to its advantageous feature of lacking proteases which avoids degradation of target protein. Usually it is used in combination with the T7-pET system where induction is performed by one point addition of IPTG. We recently published a few studies regarding lactose induction in BL21(DE3) strains. BL21(DE3) can only take up the glucose-part of the disaccharide when fed with lactose. However, initially additional glucose has to be supplied as otherwise the ATP-related lactose uptake barely happens. Yet, as lactose is an inexpensive compound compared to glucose and IPTG, a new induction strategy by a lactose-only feed during induction seems attractive. Thus, we investigated this idea in the galactose metabolizing strain HMS174(DE3). RESULTS: We show that strain HMS174(DE3) can be cultivated on lactose as sole carbon source during induction. We demonstrate that strain HMS174(DE3) exhibits higher product and biomass yields compared to BL21(DE3) when cultivated in a lactose fed-batch. More importantly, HMS174(DE3) cultivated on lactose even expresses more product than BL21(DE3) in a standard IPTG induced glucose fed-batch at the same growth rate. Finally, we demonstrate that productivity in HMS174(DE3) lactose-fed batch cultivations can easily be influenced by the specific lactose uptake rate (q(s,lac)). This is shown for two model proteins, one expressed in soluble form and one as inclusion body. CONCLUSIONS: As strain HMS174(DE3) expresses even slightly higher amounts of target protein in a lactose fed-batch than BL21(DE3) in a standard cultivation, it seems a striking alternative for recombinant protein production. Especially for large scale production of industrial enzymes cheap substrates are essential. Besides cost factors, the strategy allows straight forward adjustment of specific product titers by variation of the lactose feed rate. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-018-1016-6) contains supplementary material, which is available to authorized users.